Remote control using telephone / Badrunnisa Abd Manaf and Siti Shafinaz Ali - Abd Manaf, Badrunnisa; Ali, Siti Shafinaz (2015)
Here is a teleremote circuit which enables switching ‘on’ and ‘off ' of appliances through telephone lines. It can be used to switch appliances from any distance, overcoming the limited range of infrared and radio remote control. The circuit described here can be used to switch up to nine appliances (corresponding to the digits 1 through 9 o f the telephone key-pad). The DTMF signal on telephone instruments are used as control signals. The digit ‘0’ in DTMF mode is used to toggle between the appliances mode and normal telephone operation mode. Thus the telephone can be used to switch on or switch off the appliances also while being used for normal conversation. For our project we are advised by our supervisor to make the circuit to switch 2 appliances. The DTMF signals on telephone instruments are used as control signals.